PENGARUH VARIASI BUSI DAN BAHAN BAKAR TERHADAP PERFORMA MESIN KENDARAAN RODA DUA 135 CC - Artika, Kurnia Dwi; Imron Musthofa; Isworo, Hajar; Syahyuniar, Rusuminto; Fahriansyah, Rohmat (ELEMEN : JURNAL TEKNIK MESIN, 2023)
Spark plugs are the most important thing in the combustion system. Spark plugs in internal combustion using gasoline significantly affect vehicle performance. Likewise, fuel use must follow the compression ratio in the combustion chamber. The purpose of this study was to obtain the effect of differences in hot, cold, and medium spark plugs on engine performance and also the effect of fuel differences in supporting the performance of pertalite and pertamax two-wheeled vehicles in supporting the performance of 135 CC two-wheeled four-stroke vehicles in 2009. The result with hot spark plugs will maximizer-pm, increasing torque and power with pertalite fuel—the effectiveness of increasing power by 31%.